IN-HOSPITAL OUTCOME OF PERCUTANEOUS CORONARY INTERVENTION AFTER THROMBOLYSIS AS PART OF INVASIVE STRATEGY IN ANTERIOR ST-ELEVATION MYOCARDIAL INFARCTION - Samin, Ariz; Khan, Sajid; Anwar, Wahab; Rehmat, Samra; Bibi, Hajra; Akbar, Fazli; Kamran, Javeria; Shah, Noor; Siddiqui, Abdul Hameed; Tuyyab, Farhan (Pakistan Armed Forces Medical Journal, 2021)
Objective: In-hospital outcome of percutaneous coronary intervention after thrombolysis as part of invasive strategy in anterior ST-elevation myocardial infarction.Study Design: Cross-sectional study.Place and Duration of Study: Armed Forces Institute of Cardiology/National Institute of Heart Diseases, Rawalpindi, from Dec 2020 to Apr 2021.Methodology: Permission was sought from hospital ethics committee. Written informed consent was taken from participants of study. Charges of the tests and procedures were borne by hospital administration and not by the patient. Particulars of all the patients who meet the inclusion and exclusion criteria were recorded. Patients who present in ED after thrombolysis with streptokinase after anterior wall ST elevation myocardial infarction from any other non- percutaneous coronary intervention capable/percutaneous coronary intervention capable center were acknowledged. If the patient qualifies for facilitated percutaneous coronary intervention i.e. within 3-24 hours of fibrinolytic therapy, pathway for coronary angiogram with intent to perform percutaneous coronary intervention was initiated.Results: Total 234 patients were included according to the inclusion criteria of the study. Mean age (years) in the study was 56.71 ± 15.83 with ranges from 18-70 years. There were 164 (70.1%) male and 70 (29.9%) female patients who were included in the study according to the inclusion criteria. Out of 234 cases, 21 (8.9%) cases presented with non-fatal MI (acute stent thrombosis), 16.23% died and 4 (1.7%) stroke patients noted in patients after thrombolysis with streptokinase suffering from anterior ST-elevation myocardial infarction.Conclusion: The study concluded that those areas where percutaneous coronary intervention centers are not readily available, a pharmaco-invasive strategy can be proposed. As, this strategy comprises the use of fibrinolysis with subsequent transfer to a PCI-capable facility for angiography within 24 hours of presentation.Keywords: , , .